2012
DOI: 10.1093/gerona/glr236
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Impair Endothelium-Dependent Vasorelaxation: A Link Between Obesity and Arterial Stiffness in Very Old Zucker Rats

Abstract: To analyze age-related interactions between obesity, its associated metabolic disorders, and macrocirculation, we studied large artery stiffness and fatty acid responsiveness in lean and obese Zucker rats, aged 25 (adult) and 80 weeks (very old). Systolic arterial pressure was higher in old obese than in old lean rats (178 ± 10 vs 134 ± 8 mmHg, respectively). Carotid elastic modulus-wall stress curves showed increased age-dependent arterial stiffening, which was greater in obese animals. Old obese exhibited en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…The deleterious implication of the metabolic disorders in altering hemodynamic parameters was also suggested in other experimental models. Among others, Sloboda et al [31] demonstrated that in old obese Zucker rats had elevated plasma free fatty acid levels alter arterial stiffness was a result of endothelial dysfunction and higher systolic arterial pressure. Based on those data, it is conceivable that the early increase in FFA observed in SHHF cp/cp rats might participate in the impairment of carotid distensibility and compliance in these animals while no difference in the echocardiographic parameters could yet be detected.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious implication of the metabolic disorders in altering hemodynamic parameters was also suggested in other experimental models. Among others, Sloboda et al [31] demonstrated that in old obese Zucker rats had elevated plasma free fatty acid levels alter arterial stiffness was a result of endothelial dysfunction and higher systolic arterial pressure. Based on those data, it is conceivable that the early increase in FFA observed in SHHF cp/cp rats might participate in the impairment of carotid distensibility and compliance in these animals while no difference in the echocardiographic parameters could yet be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic alterations in vascular structure may lead to significant changes in mechanical properties, such as compliance and distensibility 3 , thus accounting for arterial stiffness, an independent risk factor for cardiovascular disease 10 . Obesity is associated with an increase in aortic pulse wave velocity (PWV) and/or intrinsic stiffness (assessed by the stress-strain relationship) in human subcutaneous small resistance arteries 6,[11][12][13] , as well as in aorta of high-fat/high-sucrose SD 7 or in genetic models of obesity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the Zucker fa/fa rat model of type 2 diabetes, mechanical, structural and molecular evidence of increased aortic stiffness before the onset of hyperglycaemia has also been reported [ 20 ]. Furthermore, aged obese Zucker rats develop also problems with distensibility with age through a left shift in the carotid elastic modulus-wall stress curves probably due to the changes in aortic composition with an increase in collagen, a decrease in elastin (thus a decrease in the elastin/collagen ratio) and an increase in dry weight due to an increase in protein content [ 19 ] ( Fig. 6.1 ).…”
Section: Obesity Diabetes and Ageingmentioning
confidence: 76%
“…It represents an ideal model for investigating the mechanisms that contribute to large artery dysfunction which occur with advanced age in obese individuals. The increase in arterial stiffness and the alteration of aortic structure are accentuated by the metabolic disorders present in the obese Zucker rat [ 19 ]. In the Zucker fa/fa rat model of type 2 diabetes, mechanical, structural and molecular evidence of increased aortic stiffness before the onset of hyperglycaemia has also been reported [ 20 ].…”
Section: Obesity Diabetes and Ageingmentioning
confidence: 97%